An Analysis on Translation Techniques in The Subtitle of The Movie “Avatar” - Ananta, I Made Wiprah (Universitas Lambung Mangkurat, 2023)
Abstract: This study investigated the intricate process of translating thoughts and ideas between different languages, which goes beyond mere linguistic proficiency. Successful translation requires a deep comprehension of cultural nuances in both the source and target languages, as well as a thorough understanding of the text and the intended audience. The aim is to achieve accurate and effective translations while avoiding literal interpretations, potential misunderstandings, and inaccuracies. The focus of this study is the specific translation techniques employed in subtitling the renowned film